Ethyl chloride spray for musculoskeletal ultrasound‐guided injections: An alternative to subcutaneous injection of local anesthetic solution. Issue 2 (4th December 2017) - Shah, Amit; Vidoni, Alessandro; McGarry, Sharon; Davies, Mark; James, Steven; Botchu, Rajesh
Abstract: Ultrasound‐guided injections such as steroid injections are common procedures involving the musculoskeletal system. They are usually performed after a subcutaneous injection of local anesthetic (LA), which can be painful. In 126 consecutive patients, local anesthesia was performed using ethyl chloride spray prior to a therapeutic ultrasound‐guided injection in joints, tendons, or bursae. Ninety‐nine (78.5%) patients found the use of ethyl chloride spray helpful. The use of ethyl chloride spray is an effective, patient‐friendly alternative to the standard injection of local aesthetic for ultrasound‐guided therapeutic musculoskeletal injections with the advantage of a lower cost of $0.18 per procedure.